2019
DOI: 10.3892/ol.2019.9918
|View full text |Cite
|
Sign up to set email alerts
|

Association between digital breast tomosynthesis and molecular subtypes of breast cancer

Abstract: In recent years, with increasing prevalence, particularly in young patients, breast cancer is considered to be one of the most common malignancies. The aim of the present study was to evaluate the clinical value of digital breast tomosynthesis (DBT) in diagnosing molecular subtypes of breast cancer. The present study retrospectively analyzed 134 cases of breast cancer with data regarding surgery, complete pathology and immunohistochemistry, which were collected at The Second Clinical College of Fujian Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Since it is a relatively recent technique, speci c features of breast cancers on DBT have indeed been scarcely described. To the best of our knowledge, only one study evaluated the appearance of breast cancers on DBT according to their histology and molecular pro le [5]. In line with our results, they showed that presence of calci cations within the tumors on DBT was more frequent in HER-2 + than in other types of breast cancers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Since it is a relatively recent technique, speci c features of breast cancers on DBT have indeed been scarcely described. To the best of our knowledge, only one study evaluated the appearance of breast cancers on DBT according to their histology and molecular pro le [5]. In line with our results, they showed that presence of calci cations within the tumors on DBT was more frequent in HER-2 + than in other types of breast cancers.…”
Section: Discussionsupporting
confidence: 76%
“…Although correlation between histology and imaging has been widely described previously on digital mammography (DM), speci c features of breast cancers on digital breast tomosynthesis (DBT) have rarely been reported. Only one recent study suggested that morphological features on DBT could be associated with molecular characteristics [5], but very little data are available to support this assertion. Breast cancer features on 2D synthetic mammography (SM) have not yet been reported, although it has been reported that the additional cancers detected with the adjunct of DBT in the screening setting would preferentially be less aggressive tumors with luminal molecular pro les [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that DBT can demonstrate the lesion margins, microcalcifications, and lymph nodes more accurately. Besides, the HER2 overexpression subtype was associated with a larger tumor size and more microcalcifications compared to the lumi- nal B subtype on DBT (21). Conversely, a recent prospective population-based study demonstrated no significant difference between DM and DBT in terms of histological subtypes (22).…”
Section: Discussionmentioning
confidence: 87%
“…As was demonstrated by prospective European studies, the addition of DBT led to an increase in cancer detection rate (CDR) from 27% to 91% [69,70]. Moreover, assistant diagnostic markers such as DBT-determined lymph node size, as well as calcification score, could be used also to determine BC molecular subtypes [71]. A comparison of TOMosynthesis with digital MammographY in the UK NHS Breast Screening Programme (TOMMY) trial showed the superior value of DBT for women with a breast density of 50% or more with sensitivity 93% and specificity 70% compared to 2D mammography (86% sensitivity and 57% specificity) [72].…”
Section: Screening and Diagnosticsmentioning
confidence: 99%